A Central Role for STAT3 in Gammaherpesvirus-Life Cycle and -Diseases - Li, Xiaofan; Bhaduri-McIntosh, Sumita (Frontiers in Microbiology, 2016)
Having co-evolved with humans, herpesviruses have adapted to exploit the host molecular machinery to ensure viral persistence. The cellular protein Signal Transducer and Activator of Transcription 3 (STAT3) is a leading example. STAT3 is a prominent transcription factor that functions in a variety of physiologic processes including embryonic development, inflammation, immunity, and wound healing. Generally activated via growth factor and cytokine signaling, STAT3 can transcriptionally drive oncoproteins, pro-survival and pro-proliferative proteins as well as angiogenic factors, thereby contributing to cancer. As in most non-viral cancers, STAT3 is constitutively active in EBV-related B and epithelial cell cancers and in animal models of KSHV-cancers. Again, similar to non-viral cancers, STAT3 contributes to gammaherpesvirus (EBV and KSHV)-mediated cancers by driving cell proliferation, invasion and angiogenesis. Being herpesviruses, EBV and KSHV establish latency in humans with episodic lytic activation. Importantly, both viruses activate STAT3 almost immediately upon infection of primary cells. In the setting of infection of primary B cells by EBV, this rapidly activated STAT3 plays a key role in suppressing the DNA damage response (DDR) to EBV-oncogene triggered replication stress, thereby facilitating B cell proliferation and ultimately establishment of latency. STAT3 also contributes to maintenance of latency by curbing lytic activation of EBV and KSHV in latent cells that express high levels of STAT3. In this way, gammaherpesviruses exploit STAT3 to overcome cellular anti-proliferative and anti-lytic barriers to promote viral persistence. These investigations into gammaherpesviruses and STAT3 have simultaneously revealed a novel function for STAT3 in suppression of the DDR, a process fundamental to physiologic cell proliferation as well as development of cancer.